WATAK HARMONIK PADA INVERTER TIGA FASA TAK BERBEBAN - Wahri Sunanda; Yuli Asmi Rahman (Foristek, 2011)
Harmonic is one of sinusoidal components, one wave period from which having multiple frequency of its fundamental frequency one, leading to electrical power quality problems. Harmonic distortion in term of voltage and current ones, generally is due to non linier impedance. Inverter is one of example of it. There are some items that will be measured. There are value ofharmonic at source and value of voltage and current harmonic when inverter does not have any load. IEEE Standard of 519-1992 as a reference in determining maximum limitation voltage and current harmonics. The result of the tests wereshowed that voltage harmonic distortion at inverter did not exceed the IEEE 519-1992 maximum limitation of 5%. Whilecurrent harmonic distortion had exceed the maximum limitation of the IEEE 519-1992. The highest results were exceeding56,55 % when inverter does not have any load.